Pulsed Current-Voltage-Induced Perturbations of a Premixed Propane/Air Flame - Jacob. B. Schmidt; Biswa. N. Ganguly (Journal of Combustion)
The effect of millisecond wide sub-breakdown pulsed voltage-current induced flow perturbation has been measured in premixed laminar atmospheric pressure propane/air flame. The flame equivalence ratios were varied from 0.8 to 1.2 with the flow speeds near 1.1 meter/second. Spatio-temporal flame structure changes were observed through collection of CH (A-X) and OH (A-X) chemiluminescence and simultaneous spontaneous Raman scattering from N2. This optical collection scheme allows us to obtain a strong correlation between the measured gas temperature and the chemiluminescence intensity, verifying that chemiluminescence images provide accurate measurements of flame reaction zone structure modifications. The experimental results suggest that the flame perturbation is caused by ionic wind originating only from the radial positive space-charge distribution in/near the cathode fall. A net momentum transfer acts along the annular space discharge distribution in the reaction zone at or near the cathode fall which modifies the flow field near the cathodic burner head. This radially inward directed body force appears to enhance mixing similar to a swirl induced modification of the flame structure. The flame fluidic response exhibit a strong dependence on the voltage pulse width ≤10 millisecond.